Tension and bonding behaviour of steel-FRP composite bars subjected to the coupling effects of chloride corrosion and load. (16th August 2021) - Ge, Wenjie; Han, MuYang; Guan, Zhongwei; Zhang, Pu; Ashour, Ashraf; Li, Wei; Lu, Weigang; Cao, Dafu; Yao, Shan
Highlights: Tensile tests and SEM were conducted to investigate the tensile properties of SFCBs. Pull-out tests were undertaken to evaluate the bonding performance of SFCBs. A bond-slip model between SFCB and concrete is developed. Abstract: Applications of steel-FRP (Fiber Reinforced Polymer) composite bar (SFCB) can overcome the corrosion problem in steel reinforced concrete (RC) structures in corrosive environment and the brittleness problem of FRP-RC structures. This paper presents an investigation on the tensile properties of SFCBs and bonding behaviour between SFCBs and concrete under chloride corrosion. The effects of fibre and reinforcement type, sustained stress level, chloride concentration and corrosion duration on the mechanical behaviour of SFCBs are analysed. The results show that SFCBs exhibit a stable post-yield stiffness with a relatively high strength retention ratio (ultimate tensile strength of the corroded specimen to that of the uncorroded specimen). For unstressed corroded tensile specimens, the strength retention ratio of FRP rebar is the highest, and that of steel rebar is the lowest, whilst those of SFCBs are in-between. Also, the strength retention ratio of the basalt SFCBs is higher than that of the glass SFCBs. The strength retention ratio decreases gradually with the increase of sustained stress level, sodium chloride concentration and corrosion duration. The bond strength retention ratios (ultimate bond stress of the corroded specimen to that of the uncorroded specimen) of the pull-out specimens are low when they are subjected to a high stress and corroded in a high concentration of sodium chloride solution, whereas the opposite is true as expected. Under the coupled action of loading and chloride corrosion, the bond strength retention ratio of steel rebar is the highest, and that of the glass SFCB is the lowest, whilst those of the basalt FRP rebar and the basalt SFCBs are in-between. Furthermore, a bond-slip model between SFCBs and concrete is developed, with the predicted bond-slip curves in good agreement with experimental ones.